Optimisation of leakage and energy in the Abbiategrasso district. Issue 1 (2nd January 2016) - Creaco, E.; Lanfranchi, E.; Chiesa, C.; Fantozzi, M.; Carrettini, C. A.; Franchini, M.
ABSTRACT: This paper presents the results of a numerical investigation aimed at attenuating leakage and energy consumption in the Abbiategrasso district, which is part of the water distribution network of Milan. Leakage minimisation, obtained as a result of service pressure reduction, was carried out on the district distribution pipes. Energy minimisation was carried out on both well pumps, which feed the district tank, and booster pumps, placed downstream of the tank. The results of the calculations showed that the application of minimisation algorithms enables obtaining significant savings in terms of pump operational costs, while guaranteeing the minimum desired pressures at all network nodes. Calculations also proved that further benefits, such as the pipe failure rate reduction, can be obtained in the Abbiategrasso district thanks to the service pressure regulation.